THE PROCEDURAL AUTONOMY OF THE MEMBER STATES AND THE PRINCIPLES OF EQUIVALENCE AND EFFECTIVENESS - Holé, Katalin (REVISTA ESMAT, 2022)
This article has as its goal to discuss the barriers of national procedural autonomy emerging in the member states of the European Union. I also discuss the legal interpretation activities of the European Court of Justice make on national procedural laws and what national codification measures the enforcement of EU law requires.